SCIENTIFIC-METHODOLOGICAL BASIS OF ARTISTIC PERCEPTION OF WORKS OF FINE ART IN HIGHER EDUCATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article analyzes the scientific-methodological foundations of artistic perception of works of fine art in higher education institutions. This research is aimed at studying the methods of developing students' artistic thinking, aesthetic taste, creative thinking and analytical skills in the process of perceiving works of art. The article also presents pedagogical approaches and methodological recommendations for teaching works of fine art.